2003
DOI: 10.1176/appi.ps.54.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients Presenting for Emergency Psychiatric Assessment at an English Hospital

Abstract: The rate of emergency referral is one indicator of the functioning of the service system as a whole. Improvements to the system should include better access to community mental health team services and a greater capacity of the primary care system to manage mental health crises. Services need to be developed that are acceptable to male patients who are experiencing social and behavioral problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…Padilha showed that the Patients with diagnoses related to the use of PAS totaled 23.8% of the patients attended by the REU Psychiatric Department of the HC-UNICAMP in this period. Similar rates were found in a study in England (28%) 12 and the United States (24.4%) 13 .…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Padilha showed that the Patients with diagnoses related to the use of PAS totaled 23.8% of the patients attended by the REU Psychiatric Department of the HC-UNICAMP in this period. Similar rates were found in a study in England (28%) 12 and the United States (24.4%) 13 .…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 89%
“…The prevalence of alcohol was also found in most studies that took place in emergency rooms. 7,12,19,20 Patients with diagnoses related to the use of PAS received more clinical and psychotropic medications than other patients attended by the Psychiatry in the REU. This picture is probably due to the fact that patients with clinical manifestations related to the use of PAS, such as intoxication and abstinence, are often in situations that require more intense clinical care.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Quite a few studies have examined the demographic and clinical characteristics of service users. Researchers have attempted to correlate these variables with outcomes such as discharge disposition, compliance with follow-up care, improved functional status, and recidivism (23)(24)(25)(26)(27)(28)(29). One particular area of research interest has been age.…”
Section: Careseeker Characteristicsmentioning
confidence: 99%
“…63 The effective participation of primary care in the mental health network decreases the overload of the network and allows for a severity grading of cases in the services involved. 64 An efficient network with strong primary care assistance relieves PESs 65 to attend only to actually necessary cases, which leads to a better management of emergency cases. 66 Primary care instruments have direct implications on PESs, avoiding the worsening of mild cases, permitting the access of more severe cases to secondary care and, thus, resulting in a decrease in the number of unnecessary hospitalizations.…”
Section: Psychiatric Emergency and Primary Carementioning
confidence: 99%